Forest, forest, forest. Sometimes we sleep. Walking, sleep, walking, sleep. It's dangerous on this way. weaponized migration landscapes at the outskirts of the European Union - Hameršak, Marijana; Pleše, Iva; Šutej, Juraj, prevoditelj (2021)
Hidden migrant routes through Croatia lead through forest areas (among other types of terrain) which include those along state borders, but also forests in the interior of the territory. Those forests can variously be seen as shelters for migrants, albeit harsh, or as green tunnels leading to desired destinations, and as scenes of suffering and violence. This article approaches the forests in question as landscapes that have been transformed from a neutral natural environment into active factors for creating and maintaining border control regimes and deterring and expelling unwanted migrants. Based on our long-term field research and publicly available (archival, media and other) sources, we seek to document, interpret, and interconnect the objects and practices involved in constructing the forest as a hostile terrain and perilous environment for migrants, and as an important element in controlling unwanted migrations. These are, on the one hand, objects and practices that intervene into forests, such as setting up cameras or cutting down trees, and, on the other, interventions that take place in forests, such as police interception or expulsion. Apart from these external interventions, in this context of remodeling forests into dangerous environments, one can also discuss the role of nature itself and its characteristics, as well as the causes of why migrants find themselves in nature in the first place. Although, at first glance, it seems that people on the move choose the forest as the place and route of their movement of their own volition, they are pushed and expelled into these forests by exclusionary policies (visa regimes, asylum systems, etc.). This, ultimately, classifies forests in Croatia as weaponized landscapes of exclusion and death, such as the desert (e.g., De León 2015), mountain (Del Biaggio et al. 2020), maritime (e.g., Albahari 2015) or archipelago (Mountz 2017) landscapes.
Skriveni migrantski putevi kroz Hrvatsku vode, među ostalim, i kroz šumske predjele koji uključuju šumska područja uz državne granice, ali i šume u unutrašnjosti teritorija. Šume se može vidjeti kao, makar i surova, skloništa za migrante ili kao zelene tunele koji vode do željenih odredišta, ali i kao poprišta stradanja i nasilja. Članak šumama o kojima je riječ pristupa kao krajolicima koji su od nepristranog prirodnog okoliša pretvoreni u aktivne činitelje stvaranja i održavanja režima kontrole granice, odvraćanja i istjerivanja neželjenih migranata. Na temelju višegodišnjih terenskih istraživanja i javno dostupnih (arhivskih, medijskih i drugih) izvora nastojimo dokumentirati, interpretirati i povezati predmete i prakse koji sudjeluju u konstruiranju šume kao neprijateljskog terena i opasnog okruženja za migrante i kao važnog elementa u kontroli neželjenih migracija. Riječ je s jedne strane o predmetima i praksama kojima se intervenira u šume, poput postavljanja kamera ili sječe stabala te s druge strane o intervencijama u šumama, poput policijskog presretanja ili protjerivanja. Osim o tim intervencijama izvana u kontekstu kreiranja šume kao opasnog okruženja može se govoriti i o ulozi same prirode i njezinih osobina, kao i o uzrocima migrantskog bivanja u prirodi. Iako se na prvi pogled čini da ljudi u pokretu sami biraju šumu za mjesto i trasu svojeg kretanja, oni su politikama isključenja (viznim režimom, azilnim sustavom i dr.) u nju gurnuti i istjerani. Time se, u konačnici, i šume u Hrvatskoj svrstavaju u naoružane krajolike isključenja i smrti poput onih pustinjskih (npr. De León 2015), planinskih (Del Biaggio et al. 2020), maritimnih (npr. Albahari 2015) ili arhipelaških (npr. Mountz 2017).
Bibliografske bilješke uz tekst ; bibliografija: str. 217-221.
Summary ; Sažetak.
Keywords: Izbjeglice -- Migranti -- Šume; Hrvatska -- EU